2012
DOI: 10.1111/j.1348-0421.2012.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of adenoviruses in Korean children hospitalized with acute gastroenteritis

Abstract: Human adenoviruses (HAdVs) are an important cause of acute gastroenteritis in children. However, few studies on the epidemiology or types of HAdVs associated with acute gastroenteritis have been conducted in Korea. Therefore, in the present study, the incidence of HAdV in 2064 stool samples from Korean children hospitalized with acute gastroenteritis (2004-2006) was assessed and the types of viruses present determined. Polymerase chain reaction, sequencing, and phylogenic analyses revealed that 113 samples (5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
6
14
1
Order By: Relevance
“…The viruses that belong to HAdV subgroup C (C1-C2-C5-C6, and C7) are known to cause respiratory viral infections [33]. Our findings corroborate those of other studies that reported the prevalence of HAdV-2 in the aquatic environment and in stool samples [34][35][36]. Taken together, these studies and others indicate that HAdV-2 is one of the serotypes most commonly excreted by humans [37], suggesting that this virus is intermittently excreted in the feces of most individuals, even if they are asymptomatic [16].…”
Section: Discussionsupporting
confidence: 90%
“…The viruses that belong to HAdV subgroup C (C1-C2-C5-C6, and C7) are known to cause respiratory viral infections [33]. Our findings corroborate those of other studies that reported the prevalence of HAdV-2 in the aquatic environment and in stool samples [34][35][36]. Taken together, these studies and others indicate that HAdV-2 is one of the serotypes most commonly excreted by humans [37], suggesting that this virus is intermittently excreted in the feces of most individuals, even if they are asymptomatic [16].…”
Section: Discussionsupporting
confidence: 90%
“…21 Vaccine coverage did not reach the entire child population of the studied community, and most children who were The present study was limited by having sequenced only the VP7 gene of RVA. However, other studies conducted in Brazil have reported the prevalence of G3, G9, and G2 as well as the emergence of unusual genotypes, such as G3P [6] and G12[P8]. 22,23 Our data showed a high diversity of HAdV subgroups associated with AGE cases.…”
Section: Discussionsupporting
confidence: 44%
“…Worldwide, RVA and NoV are the major causes of AGE, responsible for more than 400 000 deaths each year, mainly in low‐income countries . HAdVs, especially enteric viruses F40 and F41, are also associated with outbreaks and sporadic cases of AGE in children and adults …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al examined the incidence of human adenoviruses in 2064 stool samples from children hospitalized with acute gastroenteritis (2004)(2005)(2006). 11 Although 113 samples (5.5%) were positive for adenovirus, no AD-36 DNA was detected in this Korean study. 11 Therefore, despite high AD-36 seroprevalences suggesting an important circulation of AD-36 in the population, confirmation of AD-36 infection by viral culture or PCR is lacking at least in some geographic regions.…”
contrasting
confidence: 55%